Effect of the mixed ownership reform on the stock market: Evidence from China - Xi Gu; Sijia Qiao; Yishi Wang; Tianqi Song (PLoS ONE, 2025)
This study examines the effect of the mixed ownership reform from the perspective of a capital market. Based on a comprehensive dataset of Chinese state-owned enterprises (SOEs) during the period of 2006–2020, this study determines that the mixed ownership reform can decrease corporate stock price synchronicity amongst SOEs, enhancing their capital allocation efficiency. The mediation analysis reveals that the mixed ownership reform restrains the stock price synchronicity of firms by enhancing executive incentive, strengthening checks and balances amongst shareholders and reducing administration constraints in SOEs. Additional tests demonstrate that this effect is more pronounced amongst firms whose chief executive officers wield greater authority, firms whose cash flow and control rights are separated and firms with higher marketisation level. Our study adds to the literature on the governance role of the mixed ownership reform by providing evidence at the capital market level.